2005
DOI: 10.1002/jez.a.223
|View full text |Cite
|
Sign up to set email alerts
|

Triploidy in rainbow trout determined by computer‐assisted analysis

Abstract: This study was designed to assess the use of a computer-assisted system based on erythrocyte measurements as a possible alternative to flow cytometry for identifying triploid rainbow trout (Oncorhynchus mykiss). Blood smears were prepared from 26 triploid and 26 diploid specimens, as determined by flow cytometry after staining blood cells with propidium iodide. The cell and nucleus lengths of 10 erythrocytes were determined in each fish. This was followed by discriminatory analysis to distinguish between diplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
1
12
1
Order By: Relevance
“…In addition, we examined erythrocyte sizes and characteristics, which is the most applied method for detecting polyploidy in fish (Espinosa et al 2005;Maxime 2008). Cellular sizes of erythrocytes in triploids are increased due to increase in the amount of nuclear DNA (Small and Benfey 1987).…”
mentioning
confidence: 99%
“…In addition, we examined erythrocyte sizes and characteristics, which is the most applied method for detecting polyploidy in fish (Espinosa et al 2005;Maxime 2008). Cellular sizes of erythrocytes in triploids are increased due to increase in the amount of nuclear DNA (Small and Benfey 1987).…”
mentioning
confidence: 99%
“…Females resulted from breeding of females (XX) and males (XY), and these females were verified by morphological characteristics. Triploid females originated from eggs fertilized with semen from neomales (XX), and hydrostatic pressure shock was applied to eggs shortly after fertilization (750 atmospheres/cm 2 ), using an automatic system designed in a previous study in our laboratory (Patent P200300079, Espinosa et al. 2005, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has demonstrated that polyploids possess larger erythrocytes (Licht and Bogart 1987;Boron 1994), and that the nuclear and cell size of erythrocytes uniformly increases with the level of ploidy (Small and Benfey 1987;Wolters et al 1982). Hence, the size of erythrocytes has been used as a criterion to identify ploidy (Small and Benfey 1987;Espinosa et al 2005;Harrell et al 1998;Thorgaard et al 1982;Pierrez and Ronot 1991;Cassani et al 1990). However, all these earlier data have been gained only from diploids and triploids, with no reports on higher ployploidy levels.…”
Section: Relationship Between Ploidy and Size Of Erythrocytesmentioning
confidence: 98%
“…Moreover, the main factor involved in the increased size of red blood cells in triploid Atlantic salmon is the increase in cell length, whereas cell width and height remain unchanged . The nuclear volumes of erythrocytes have also been used to identify the ploidy levels in fish in several studies ; (Espinosa et al 2005). In addition, compared with the erythrocytes of diploid fish, the erythrocytes of polyploid fish have obvious differences in the shape of the cell and its nucleus and in the number of cells (Zhu et al 1992;Liu et al 2004).…”
Section: Introductionmentioning
confidence: 99%